Analisis Minat Masyarakat Non Muslim tentang Perbankan Syariah dari Tahun Ke Tahun di Indonesia - Faisal Fahmi; Muhammad Habibi Siregar (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Islamic banks in terms of their current development are not lagging behind with progress as well as conventional banks. Conventional banking that implements an interest system goes side by side with Islamic banking that implements a profit-sharing system. The problem faced by Islamic banks is the low public knowledge about Islamic banking, especially caused by the dominance of conventional banking so that Islamic banking is still underestimated. The purpose of this study is to find out how the public understands Islamic banking in Adi Jaya Village, Flygi Besar District, Central Lampung Regency. This type of research is field research conducted in Kampung Adi Jaya. The nature in this study is a qualitative descriptive method. There are two sources of data in this study, namely primary data sources and secondary data sources. The primary data source is obtained directly from the community, while the secondary data source that the researchers use is in the form of Kampung Adi Jaya documents and from various books. To obtain valid data, researchers use a data collection method, namely interviews. After the data is collected, the researcher analyzes using qualitative data analysis techniques using inductive methods.. The results of field research show that the understanding of the public about Islamic banks in Kampung Adi Jaya is that people only know the existence of Islamic banks but do not understand Islamic banks in detail. Only some people understand about Islamic banks and some even don't know about Islamic banks at all. Most people do not know what products and services are available in Islamic banks. Lack of understanding from the public due to the lack of information obtained from Islamic banks and media such as television, print media and social media which causes people not to know what Islamic banks are and what products are in Islamic banks.